FACIAL GROWTH PATTERNS BY J. JARABAK IN PATIENTS WITH DISTAL BITE AND THEIR DIAGNOSTIC VALUE - S.I. Doroshenko; O.Y. Opekha; V.V. Volkova (Український стоматологічний альманах)
Purpose. To determine the features of the structure of the facial skeleton in patients with DB, taking into account its growth patterns and rotation.